The Use of Digital Media to Enhance Arabic Writing Skills at Madrasah Aliyah: a Qualitative Study - Ade Arip Ardiansyah; Aneu Masripah; Firdan Agustiana (Gunung Djati Conference Series, 2026)
This study aims to examine the use of digital media in enhancing Arabic writing skills at Madrasah Aliyah. A descriptive qualitative method was employed to provide an in-depth description of how digital media are utilized in Arabic writing instruction. Primary data were collected through interviews, observations, and analysis of teacher and student writing tasks, while secondary data were obtained from school documents and relevant literature. Data collection techniques included semi-structured interviews, participatory observations, and documentation. Data analysis followed the Miles and Huberman model through ongoing processes of data reduction, data display, and conclusion drawing. The findings reveal that digital media such as Google Docs, Google Classroom, WhatsApp, Padlet, Canva, and educational videos greatly support Arabic writing instruction at Madrasah Aliyah. These tools facilitate material delivery, writing practice, and rapid feedback through digital comments. Both teachers and students hold positive perceptions, as digital media enhance understanding of sentence structure, vocabulary acquisition, and motivation. Despite challenges related to devices and internet connectivity, the use of digital media has been proven to improve students’ linguistic accuracy, paragraph coherence, creativity, and self-confidence.